REALIZATION OF DECISION MAKING IN THE TRANSLATION PROCESS OF THE WEB CONTENT OF www.ayodya.com - Sigalingging, Bob M. (Universitas Gunadarma, 2017)
Website translation is a kind of translation evolving in recent years along with the advancement in information technology. The realization of decision making in the translation process of web content of www.ayodyapala.com is actually a process of problem solving in communication involving Bahasa Indonesia as the source language (SL) and English as the target language (TL). This study aims to identify a number of translation techniques used by the translator to translate the content of www.ayodyapala.com and also describe the translation process of it. This research is descriptive-qualitative and process-oriented in the field of translation. The data used in this study are linguistic elements including words, phrases, and sentences provided in the www.ayodyapala.com. The sampling technique applied was purposive sampling and the technique of data collection was content analysis. The analysis results demonstrate that first, there are 14 translation techniques used in translating the content of www.ayodyapala.com, namely literal translation, transposition, borrowing, established equivalence, modulation, reduction, adaptation, amplification, particularization, generalization, linguistic compression, discursive creation, linguistic amplification, and calque. Second, the translation process of www.ayodyapala.com is reflected through translation procedures consisting of transposition, modulation, naturalization, contextual conditioning, and notes. Keywords: Translation technique, translation process, web content, source language,target language.